2017
DOI: 10.1038/nutd.2016.51
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of a beverage containing bitter melon extract (CARELA) on postprandial glycemia among prediabetic adults

Abstract: Background:Acute ingestion of bitter melon (BM) has been shown to suppress the postprandial glycemic response in diabetics, but its impact on glucose regulation among individuals with impaired glucose tolerance is unclear. Moreover, one's glucose tolerance level may influence the effectiveness of BM. This study aimed to examine the acute effects of a beverage containing BM extract on blood glucose regulation during an oral glucose tolerance test (OGTT) among prediabetics.Methods:Ten prediabetic adults complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Clinical studies have also revealed that depending on the degree of glucose tolerance in individuals defined by various glucose response indices including glucose curve shapes, they may either be responders or non-responders to a given intervention such as with natural plant extracts [34][35][36][37]. Krishnan and colleagues have also emphasised the importance of examining dietary interventions using an integrated physiological approach that stratified participants with varying glycaemic responses into subgroups in contrast to overall group responses [37].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies have also revealed that depending on the degree of glucose tolerance in individuals defined by various glucose response indices including glucose curve shapes, they may either be responders or non-responders to a given intervention such as with natural plant extracts [34][35][36][37]. Krishnan and colleagues have also emphasised the importance of examining dietary interventions using an integrated physiological approach that stratified participants with varying glycaemic responses into subgroups in contrast to overall group responses [37].…”
Section: Introductionmentioning
confidence: 99%
“…Our data also demonstrate that when compared to soy isoflavone or genistein which is currently available in the market, MME improves the serum HDL level, atherogenic index, and oxidative stress status better than soy isoflavone does. In addition, MME treatment especially at low and medium doses for 8 weeks also increases glycemic control capability reflected by the reduction in plasma glucose AUC [70]. The possible explanation may be associated partly with the protection of active ingredients such as polyphenolic compound including cyanidins by a core material which is used for encapsulation [71, 72].…”
Section: Discussionmentioning
confidence: 99%
“…In 2012, a study focused on 42 metabolic syndrome patients reported that bitter gourd treatment for three months evidently decreased the incidence of metabolic syndrome, which is recognized for predicting T2DM, and the improvement could remain for one month after stopping supplement [ 107 ]. An acute experiment in prediabetic adults exhibited that acute intake of bitter melon beverage led to the reduction of postprandial glucose in 50% of the subjects [ 108 ]. Next year, a RCT on 52 individuals with prediabetes showed that MC intake dropped the blood glucose in participants with higher baseline FBG levels more significantly [ 109 ].…”
Section: Clinical Trialsmentioning
confidence: 99%